(untitled) - Ash, Robert B. (San Diego, California, 2000)
Probability and Measure Theory, Second Edition, is a text for a graduate-level course in probability that includes essential background topics in analysis. It provides extensive coverage of conditional probability and expectation, strong laws of large numbers, martingale theory, the central limit theorem, ergodic theory, and Brownian motion.,Probability and Measure Theory, Second Edition, is a text for a graduate-level course in probability that includes essential background topics in analysis. It provides extensive coverage of conditional probability and expectation, strong laws of large numbers, martingale theory, the central limit theorem, ergodic theory, and Brownian motion.
Độ đo và tích phân LơBe,Thống kê phép thí nghiệm - CNTP,Các định lý giới hạn,Lý thuyết độ đo và tích phân
Keywords: Mesure theory,Probability